Correlated Quantum Tunneling of Monopoles in Spin Ice - Tomasello, Bruno; Castelnovo, Claudio; Moessner, Roderich; Quintanilla, Jorge (Physical review letters, 2019)
The spin ice materials Ho_{2}Ti_{2}O_{7} and Dy_{2}Ti_{2}O_{7} are by now perhaps the best-studied classical frustrated magnets. A crucial step towards the understanding of their low temperature behavior-both regarding their unusual dynamical properties and the possibility of observing their quantum coherent time evolution-is a quantitative understanding of the spin-flip processes which underpin the hopping of magnetic monopoles. We attack this problem in the framework of a quantum treatment of a single-ion subject to the crystal, exchange, and dipolar fields from neighboring ions. By studying the fundamental quantum mechanical mechanisms, we discover a bimodal distribution of hopping rates that depends on the local spin configuration, in broad agreement with rates extracted from experiment. Applying the same analysis to Pr_{2}Sn_{2}O_{7} and Pr_{2}Zr_{2}O_{7}, we find an even more pronounced separation of timescales signaling the likelihood of coherent many-body dynamics.